A new approach to detecting shill bids in e-auctions. (20th April 2007) - Matsuo, Tokuro; Ito, Takayuki; Shintani, Toramatsu
False-name bids and shill bids pose an emerging problem for auctions. To solve the problem, we propose a new method for finding shill bid in order to avoid them. Our algorithm can judge whether there might be a shill bid from the results of the bidding procedure. Further, in this paper, we propose an improved method, which can dramatically reduce the computational cost. The results demonstrate that the proposed method successfully reduces the computational cost needed to find shill bids. The contribution of our work is in the integration of the theory and detecting fraud in combinatorial auctions.